Bethelsdorp c.1890-1945 : verstedelikingsverskynsels in 'n periferiegebied (Historia, 2021)
Bethelsdorp c.1890-1945: Urbanisation phenomena in a peripheral area. Although this former missionary institution was a peri-urban area during the period under discussion, it did indeed experience the effect of the urbanisation process in Port Elizabeth. This can be seen on two levels: reality and perception. Being on the fringe of an expanding city, Bethelsdorp served as an early 20th century refuge for Coloureds and Blacks who either could not or preferred not to obtain controlled and more expensive housing within the municipal area. Migration to a place of residence at greater distance from the urban working place had thus become a personal choice for many before apartheid legislation institutionalised it into an urban pattern. The well-known urban slums did not develop in the Bethelsdorp settlement. Nevertheless, the increasing influx did create mounting pressure on the existing residential and hygienic facilities and services. The financial and administrative inability of first the Council of Supervisors and then the Local Board, as town councils, to cope effectively with the situation elicited negative comments on the settlement. But seen in a comparative perspective, much of this was impressionistic and formulated exclusively in terms of White urban interests, reminding of a ""sanitation syndrome"" kind of response.
Keywords: Sanitation; Demography; Coloureds; Urbanization; Blacks; Socio-economic developments; Health; Housing; Port Elizabeth; Bethelsdorp; Economics; Peripheral areas